Gender Differentials in Labor Market Outcomes - Antecol, Heather (My University, 1998)
In this dissertation, I study three aspects of gender differentials in labor market outcomes. The first essay examines why there is inter-ethnic variation in the gender wage among the first generation, and among second-and-higher generation immigrants to the United States. Using the 1990 U.S. Census I contrast the role of human capital factors and "cultural" factors, i.e. differences in preferences regarding family structure and women's role in market versus home work. While human capital factors do play an important role, especially among second and higher generation immigrants, controlling for these factors does not eliminate inter-ethnic variation in the gender wage gap. In fact, for first generation immigrants, I find that even after controlling for all observable characteristics in the United States, a one percentage point increase in the home country gender wage gap is associated with a 0.9 percentage point increase in the gender wage gap across these ethnic origin groups in the United States. I argue that this positive correlation suggests the importance of cultural factors. Although I am unable to detect the effect of home country factors for second-and-higher generation immigrants, there appears to be a role for "tastes" regarding work and family, in addition to the more commonly-analyzed human capital and institutional factors, in explaining why some women earn more relative to men than others. The second essay attempts to measure the effect of employment equity laws on job search outcomes, and on perceptions of discrimination by both men and women in a sample of Canadian job seekers. I find some evidence that employment equity coverage in a preseparation job reduces the relative amount of time it takes women, versus men, to become re-employed. This effect operates largely through highly significant differences in the rate at which women and men are recalled to the preseparation employer. Finally, I find that employment equity coverage reduces the gender gap in the extent to which workers feel harmed by gender discrimination. Perhaps unfortunately, this effect primarily occurs via an increase in men's perceptions of being harmed, rather than a reduction in women's. The final chapter seeks to explain why, compared to older women, young female job seekers are more than three time as likely to report that their ability to find a good new job is compromised by the simple fact that they are female. Using the same sample of job seekers as in Chapter 2, I show, first, that young women's more frequent reports of gender-induced harm cannot be statistically attributed to any observed personal or job characteristics, or to any "objective" measure of discrimination computable in my data. Second, using new questions asked in the aforementioned survey, I note that women's reports of gender-induced advantage, as well as men's reports of gender-induced harm, are also more prevalent among the young. Using a formal model of the reporting decision, I conclude that the most likely cause of all these phenomena is a particular kind of age difference in reporting behavior: young people of both sexes are more likely than older people to interpret departures in either direction from gender-neutral treatment as casually affected by their gender. This may have important implications for future public support of anti-discrimination policies, and for the design of those policies.
Keywords: Economics; Economics